Design of Efficient Off-Grid Solar Photovoltaic Water Pumping System Based on Improved Fractional Open Circuit Voltage MPPT Technique. (14th October 2021) - Hmidet, Ali; Subramaniam, Umashankar; Elavarasan, Rajvikram Madurai; Raju, Kannadasan; Diaz, Matias; Das, Narottam; Mehmood, Kashif; Karthick, Alagar; Muhibbullah, M.; Boubaker, Olfa
Abstract : The main application of off-grid solar photovoltaic (SPV) systems is water extraction in rural areas where access to the grid is restricted. In this application, photovoltaic (PV) and pump system regulation are crucial to increase its overall efficiency. In this context, this work presents a simple and efficient off-grid SPV water pumping system (SPVWPS). The designed system is based on a DC-DC boost converter, a three-phase DC-AC inverter, and a three-phase induction motor (IM) coupled to the centrifugal pump. The proposed solution is operated using a control strategy that associates an improved fractional open-circuit voltage (FOCV) method for maximum power point tracking (MPPT) and closed-loop scalar control. This association avoids the use of a speed sensor/encoder and a current sensor for the IM. Finally, the effectiveness of the proposed off-grid SPVWPS and its control system for both steady-state and dynamic conditions of insolation change is verified using a 1KVA rated prototype. The relevance of the drive is also checked in various operating conditions and is found to be adequate for pumping water. Moreover, the proposed method guarantees a fast response, less oscillations around the MPP, a system efficiency of 99%, and a high flow rate due to the extraction of maximum power.